Regeneration of the Corneal Epithelium after Debridement of its Central Region: An Autoradiographic Study on Rabbits - Barbosa, Flavia Leao; de Faria-e-Sousa, Sidney Julio; Goes, Rejane Maira [UNESP]; Haddad, Antonio (Taylor & Francis Inc, 2009)
Purpose: To investigate the proliferative behavior of the corneal and limbal epithelia after debridement on the central region of the rabbit cornea. Methods: After scraping a circular epithelial area, 5 mm in diameter, in the center of the cornea, (3)H-thymidine ((3)H-TdR) was injected intravitreally, and the rabbits killed from 1 to 49 days afterward. The cornea, together with the adjacent conjunctiva, was processed for autoradiography. Results: The regenerating epithelium at the center of the cornea exhibited high frequencies of labeled nuclei when compared to controls. The mitotic indexes for the limbus were comparable in experimental and control eyes. The unique basal stratum of the limbal epithelium exhibited quick proliferation and vertical migration in all eyes. Cells that remained labeled for four weeks or more were observed throughout the corneal epithelium, including its basal stratum, and this did not depend on epithelial damage. Conclusion: Corneal epithelium wounds are healed by sliding and proliferation of cells surrounding the epithelial gap without any evidence for the participation of the limbal epithelium. Daughter cells labeled with (3)H-TdR were visualized in all layers of the corneal epithelium up to 7 weeks after the DNA precursor injection. However, at this long interval, the only labeled cells in the limbus were in the suprabasal layers.
Keywords: autoradiography; cornea; debridement; epithelium; label-retaining; limbus; rabbits; stem cell